A case report and literature review on positive outcomes achieved through radiotherapy in a patient with composite hemangioendothelioma - Zhang, Fei; Luo, Cha; Zeng, Ying; Wang, Zhonglian; Jiang, Hongting; Ye, Qing; Jian, Wei; Zhang, Jing; Fu, Qiaofen (Frontiers in Oncology, 2025)
BackgroundComposite hemangioendothelioma (CHE) is a rare borderline vascular neoplasm, typically characterized by a heterogeneous composition of benign, intermediate, and malignant vascular elements. Metastasis occurs occasionally, yet local recurrence remains relatively common. CHE frequently manifest in the deep dermis and subcutaneous soft tissues of the distal limbs, and are rarely observed in bone or vertebral column. We present a case that originally occurred in the lumbar spine.Case presentationA 75-year-old male patient presented with progressively worsening pain in the lumbar and gluteal regions, accompanied by impaired mobility. Lumbar spine MRI and PET-CT imaging revealed abnormal signals in the left side of the L5 vertebral body and the left pedicle, indicative of potentially aggressive pathological changes. Pathological biopsy under general anesthesia confirmed a diagnosis of CHE. Given the impossibility of completely resecting the lesion, the patient underwent radiation therapy. After a course of radiotherapy (60Gy/30 fractions), the patient was discharged from the hospital. The patient has been followed up for a period of 20 months with no evidence of recurrence.ConclusionCHE refers to a rare type of tumor that rarely involves the spine. We present a case of CHE occurring in the L5 vertebral body. Given the lack of definitive indications for surgical intervention, radiation therapy was administered, resulting in highly satisfactory therapeutic outcomes and an excellent prognosis.